Work Engagement among Taman Pendidikan Al-Qur’an’s Teachers: The Role of Religiosity - Apriasari, Hastinia; Susetyo, Yuli Fajar (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
Work engagement is essential for non-formal education teachers, including Taman Pendidikan Al-Quran (TPA) teachers. Work engagement will improve the work performance of TPA teachers. The religiosity of TPA teachers is expected to play a key role in increasing work engagement. This study aims to examine the contribution of religiosity toward work engagement. The hypothesis proposed in this study is that religiosity can predict the level of work engagement. The subjects of this study are the TPA teachers, consisting of 84 females and 70 males who have a year of teaching experience minimally. The instrument used to collect the data is the Utrecht Work Engagement Scale (UWES) which has been modified, and the religiosity scale as well. Data are analyzed by simple regression analysis. Religiosity plays a role in 30.4 % of teachers’ work engagement. In addition, the dimension of religiosity has the most significant role in the work engagement of the TPA teachers. The result shows that religiosity can predict work engagement for the TPA teachers.